Hip Fracture Surgery vs Elective Total Hip Replacement - Metcalfe, D; Perry, D; Costa, M (American Medical Association, 2016)
In their recent observational study, Le Manach et al1 used a 1:1 matching technique and found that the relative risk of in-hospital mortality is higher for hip fracture patients than those undergoing elective total hip replacement (THR). The authors conclude that this difference cannot be adequately explained by patient characteristics and so probably represent “physiologic mechanisms, such as acute stress and inflammatory states resulting from the fractures”. This conclusion is however difficult to justify given the enormous differences between elective and trauma populations. Elective THR patients are selected for their suitability to undergo a major operation whereas hip fractures are typically a consequence of physiological deterioration (osteoporosis and falling).